PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DENGAN KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI VARIABEL MODERASI PADA PT. GAPURA ANGKASA DENPASAR - I Komang Triyana Dharma; I Wayan Sujana; Ni Nyoman Ari Novarini (EMAS, 2021)
Employee performance at PT. Gapura Angkasa Denpasar has an important role in achieving company goals. Employee performance level at PT. Gapura Angkasa Denpasar in the operational unit is suspected of experiencing stagnation, because the level of employee career development is still lacking which is also influenced by the factor of leadership. This research aims to determine and analyze the effect of career development on employee performance at PT. Gapura Angkasa Denpasar with transformational leadership as moderator. The study population was part of the employees at PT. Gapura Angkasa Denpasar Operational Unit with a sample of 56 employees who were determined based on the Slovin method. The analytical tool used is SEM (Structural Equation Modeling) with the application of the Partial Least Square (PLS) program. The results showed that career development has a positive and significant effect on employee performance at PT. Singapore Angkasa Denpasar, transformational leadership has a positive and significant effect on the relationship between career development and employee performance.